2006
DOI: 10.1103/physrevlett.96.196405
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of One-Dimensional Interacting Fermions

Abstract: We evaluate the dynamic structure factor S(q, ω) of interacting one-dimensional spinless fermions with a nonlinear dispersion relation. The combined effect of the nonlinear dispersion and of the interactions leads to new universal features of S(q, ω). The sharp peak S(q, ω) ∝ qδ(ω − uq), characteristic for the Tomonaga-Luttinger model, broadens up; S(q, ω) for a fixed q becomes finite at arbitrarily large ω. The main spectral weight, however, is confined to a narrow frequency interval of the width δω ∼ q 2 /m.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
303
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(326 citation statements)
references
References 17 publications
19
303
2
2
Order By: Relevance
“…[4][5][6][7][8] In addition, ultracold atoms trapped in optical lattices have emerged as a new means to study coherent dynamics of 1D models, including integrable ones which are not realizable in condensed matter systems. 9 At the same time, significant progress has been achieved in developing analytical [10][11][12][13][14][15][16][17][18][19][20][21][22] and numerical [23][24][25] techniques to study dynamical correlation functions in the high energy regime where conventional Luttinger liquid theory 26,27 does not apply. Analytically, it is possible to compute exponents of power-law singularities that develop near thresholds of the spectrum of dynamical correlation functions at arbitrarily high energies.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] In addition, ultracold atoms trapped in optical lattices have emerged as a new means to study coherent dynamics of 1D models, including integrable ones which are not realizable in condensed matter systems. 9 At the same time, significant progress has been achieved in developing analytical [10][11][12][13][14][15][16][17][18][19][20][21][22] and numerical [23][24][25] techniques to study dynamical correlation functions in the high energy regime where conventional Luttinger liquid theory 26,27 does not apply. Analytically, it is possible to compute exponents of power-law singularities that develop near thresholds of the spectrum of dynamical correlation functions at arbitrarily high energies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a continuum of collective excitations is found in [27,28] for a certain frequency range, ω − < ω < ω + , where ω ± are q- and interaction-dependent. In addition, spectral weight is shifted (for a repulsive interaction) to the lower end of the continuum, leading to a power-law divergence near ω − .…”
Section: Numerical Results Inmentioning
confidence: 99%
“…In addition, in the exact data more and more spectral weight is shifted down to the left sub-peaks of the low energy doublets, a feature which is not obtained within CDFT-LDA. The transfer of spectral weight to lower frequencies eventually leads to the formation of the power-law divergence at the lower end of the continuum in the infinite system [27,28].…”
Section: Numerical Results Inmentioning
confidence: 99%
“…In recent papers [56][57][58][59] it was shown that neglecting irrelevant operators perturbing the Luttinger liquid Hamiltonian can lead to incorrect results for on-shell singularities in correlation functions. Introducing a coupling to a mobile impurity and taking the leading irrelevant operators into account nonperturbatively it is possible to recover the exact singularity threshold and critical exponent.…”
Section: Conformal Towersmentioning
confidence: 99%